Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s10350-006-0714-z
|View full text |Cite
|
Sign up to set email alerts
|

Indication and Benefit of Pelvic Sidewall Dissection for Rectal Cancer

Abstract: Positive lateral lymph node was the strongest predictor in both survival and local recurrence. Pelvic sidewall dissection may be indicated for patients with T3-T4 lower rectal cancers because of the greater probability of positive lateral lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
287
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 391 publications
(304 citation statements)
references
References 38 publications
11
287
2
4
Order By: Relevance
“…The incidence of LPLN-positive status (18.3%) in our study was similar to that of pathological LPLN metastasis of previous reports, in which patients underwent surgery alone (1)(2)(3)(4)(5). Following preoperative CRT, 7 of the 19 (36.8%) initially LPLN-positive patients exhibited LPLN downsizing to <7 mm; none of these 7 patients developed recurrence.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The incidence of LPLN-positive status (18.3%) in our study was similar to that of pathological LPLN metastasis of previous reports, in which patients underwent surgery alone (1)(2)(3)(4)(5). Following preoperative CRT, 7 of the 19 (36.8%) initially LPLN-positive patients exhibited LPLN downsizing to <7 mm; none of these 7 patients developed recurrence.…”
Section: Discussionsupporting
confidence: 88%
“…Multivariate analysis are ~45% (2,3,16,17), which are inferior to that of our patients with enlarged LPLN after CRT who had TME alone. Although the survival rates of the present study cannot be compared to previously reported rates, a proportion of patients with LPLN metastasis may clearly be treated by CRT-TME alone.…”
Section: Univariate Analysiscontrasting
confidence: 77%
See 1 more Smart Citation
“…It was reported that local recurrence can be found in 4%-50% of patients with rectal carcinoma after curative resection, and lateral lymph node metastasis may be the important factor for local recurrence [15,16] . Ueno et al [15] reported that patients with lateral node metastases have an increased risk for local recurrence (44% vs 11.7%; P < 0.001) compared with those without lateral node metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The survival of patients with advanced low rectal cancer www.wjgnet.com still remains poor. It was reported that lateral lymph node metastasis may be the most important factor for local recurrence and poor prognosis of advanced low rectal cancer [15][16][17][18] . In the current study, the data on 96 consecutive patients who underwent curative surgery with total mesorectal excision and lateral lymph node dissection for advanced low rectal cancer at the Department of General Surgery of Guangdong Provincial People's Hospital were retrospectively analyzed.…”
Section: Introductionmentioning
confidence: 99%